Comparing Emotional Development in Persons With Intellectual Disability With and Without Autism Spectrum Disorder. - Hermann, Hauke; Witte, Annemieke M.; Pöhlmann, Anna; Sterkenburg, Paula S.; Sappok, Tanja (Journal of Intellectual Disability Research, 2025)
Background: Intellectual disability (ID) often co‐occurs with autism spectrum disorder (ASD). To better understand the needs of persons with ID/ASD, level of emotional development (ED) can be determined with the Scale of Emotional Development‐Short (SED‐S). This preregistered study examined differences in ED by comparing total, domain, and item scores between people with ID/ASD and people with ID. Methods: One hundred seventy‐four participants with ID/ASD were matched to 174 participants with ID only. Informants reported on the SED‐S, which includes 200 yes‐no items grouped into eight domains, with each domain including five stages of ED. Results: The ID/ASD group showed lower total scores (M = 2.19, SD = 0.97) compared with the ID group (M = 2.86, SD = 1.11). They also showed lower scores in all eight domains. When groups were compared based on total scores, people with ID/ASD in SED‐S 2 scored lower in the domain Affect, while those in SED‐S 3 scored lower in the domains Affect, Communication, and Peers compared with people with ID in the same stage. People with ID/ASD in SED‐S 4 scored higher in the domain Peers compared with people with ID in the same stage. There was an uneven distribution of 'yes' responses, significant differences in 'yes' responses to 27 items, and a lower mean frequency of 'yes' responses from people with ID/ASD. Conclusions: Although this study was largely exploratory and warrants replication, results provide an important next step towards a better understanding of the emotional needs and behaviours of people with ID/ASD.